2021
DOI: 10.1371/journal.ppat.1008866
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic glycolysis supports hepatitis B virus protein synthesis through interaction between viral surface antigen and pyruvate kinase isoform M2

Abstract: As an intracellular pathogen, the reproduction of the hepatitis B virus (HBV) depends on the occupancy of host metabolism machinery. Here we test a hypothesis if HBV may govern intracellular biosynthesis to achieve a productive reproduction. To test this hypothesis, we set up an affinity purification screen for host factors that interact with large viral surface antigens (LHBS). This identified pyruvate kinase isoform M2 (PKM2), a key regulator of glucose metabolism, as a binding partner of viral surface antig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Other evidence for redox regulation of viral protein activity is illustrated by the observation that glutathionylation of cysteine residues Cys 67 and Cys 95 modulates HIV-1 protease activity [30]. Redox regulation of HIV-1 protease activity is believed to allow timely virus maturation and prevents premature host cell death, given the ability of this viral protein to cleave host prosurvival Bcl-2 protein [31].…”
Section: Oxidative Modification Of Viral Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidence for redox regulation of viral protein activity is illustrated by the observation that glutathionylation of cysteine residues Cys 67 and Cys 95 modulates HIV-1 protease activity [30]. Redox regulation of HIV-1 protease activity is believed to allow timely virus maturation and prevents premature host cell death, given the ability of this viral protein to cleave host prosurvival Bcl-2 protein [31].…”
Section: Oxidative Modification Of Viral Proteinsmentioning
confidence: 99%
“…Control of ROS production through metabolic switch Metabolic reprogramming has long been known as a viral strategy to generate all the molecules and metabolites necessary for optimal virus production [64]. More specifically, several viruses, such as HBV, HCV, HIV-1, and SARS-CoV2, have been reported to induce a metabolic switch to aerobic glycolysis in a manner reminiscent of the Warburg effect observed in cancer [65][66][67][68]. The metabolic switch to aerobic glycolysis has been described as an important underlying mechanism to ensure the generation of anabolic intermediates required for proliferation of cancer cells, and likely serves a similar function during viral infection for the synthesis of viral progeny.…”
Section: Biphasic Modulation Of Ros Productionmentioning
confidence: 99%
“…HBV has been shown to induce metabolic reprogramming to provide energy for HBV replication [ 6 , 7 , 8 ]. HBV infection increases glucose uptake, glycolytic metabolism, and lipid accumulation, which drive hepatic tissue damage resulting in the development of cirrhosis and HCC [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection increases glucose uptake, glycolytic metabolism, and lipid accumulation, which drive hepatic tissue damage resulting in the development of cirrhosis and HCC [ 9 , 10 , 11 ]. Although many metabolic proteins are involved in HBV replication [ 6 , 7 , 8 , 9 , 10 , 11 ], the underlying signaling pathway associated with metabolism during HBV replication has not yet been clearly determined. Evaluation of the metabolic signaling pathways associated with HBV replication showed that the AMPK activator metformin, which is used to treat patients with type 2 diabetes, suppressed the syntheses of HBe and HBs antigens and HBV replicative intermediate (RI) DNAs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This effect initially occurs in tumor cells and is called the “Warburg” effect. Many studies have reported that aerobic glycolysis occurs in microglia ( Cheng et al, 2021a ; Wang et al, 2021a ), NK cells, and monocytes under different pathological conditions ( Cheng et al, 2016 ; Sheppard et al, 2021 ) and even virus-infected macrophages ( Wu et al, 2021 ). It is found that the serum and neutrophils of SARS-CoV-2 patients contain high lactate content, which is caused by elevated glycolysis ( McElvaney et al, 2020 ; Jia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%